Production of reactive oxygen species after photodynamic therapy by porphyrin sensitizers - Kolářová, Hana; Nevřelová, Pavla; Tománková, Kateřina; Kolář, Petr; Bajgar, Robert; Mosinger, Jiří (General physiology and biophysics, 2008)
The objectives of this study was to investigate the production of reactive oxygen species (ROS) after photodynamic therapy (PDT) in vitro. We examined second generation sensitizers, porphyrines (TPPS4, ZnTPPS4 and PdTPPS4) and compared their effectivity on ROS generation in G361 cell line. Used porphyrines are very efficient water-soluble aromatic dyes with potential to use in photomedicine and have a high propensity to accumulate in the membranes of intracellular organelles like lysosomes and mitochondria. Interaction between the triplet excited state of the sensitizer and molecular oxygen leads to produce singlet oxygen and other ROS to induce cell death. Production of ROS was verificated by molecular probe CM-H2DCFDA and viability of cells was determined by MTT assay. Our results demonstrated that ZnTPPS4 induces the highest ROS production in cell line compared to TPPS4 and PdTPPS4 at each used concentration and light dose. These results consist with a fact that photodynamic effect depends on sensitizer type, its concentration and light dose.
Keywords: Photochemotherapy; fotosenzibilizující látky; fotochemoterapie; Cell Line, Tumor; Photosensitizing Agents; reaktivní formy kyslíku; Palladium; Melanoma; Reactive Oxygen Species; palladium; lidé; Humans; Porphyrins; Financing, Organized; zinek; porfyriny; nádorové buněčné linie; financování organizované; melanom; Zinc